2002
DOI: 10.1128/jvi.76.11.5395-5403.2002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Tumor Necrosis Factor Alpha Promoter by Human Parvovirus B19 NS1 through Activation of AP-1 and AP-2

Abstract: Human parvovirus B19 frequently causes acute and chronic arthritis in adults. The molecular mechanism of B19 arthritis, however, remains poorly understood. We previously showed that the transmission of B19 from rheumatoid synoviocytes to monocytic cells is associated with enhanced secretion of tumor necrosis factor alpha (TNF-␣), which triggers inflammation, and interleukin-6. To determine the role of B19 in the production of TNF-␣, we focused on the function of its nonstructural protein, NS1, and established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 70 publications
1
64
1
2
Order By: Relevance
“…It has been shown to possess sitespecific DNA-binding and helicase activities, and is functionally active as a trans-activator of the viral p6 and various cellular promoters (Gareus et al, 1998;Raab et al, 2001Raab et al, , 2002Vassias et al, 1998), for example, the cellular promoters for the expression of TNF-a and interleukin 6 (Fu et al, 2002;Moffatt et al, 1996). NS1 also contains a well-conserved nucleoside-triphosphate-binding motif, which is essential for a variety of biological functions, such as ATPase activity and cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to possess sitespecific DNA-binding and helicase activities, and is functionally active as a trans-activator of the viral p6 and various cellular promoters (Gareus et al, 1998;Raab et al, 2001Raab et al, , 2002Vassias et al, 1998), for example, the cellular promoters for the expression of TNF-a and interleukin 6 (Fu et al, 2002;Moffatt et al, 1996). NS1 also contains a well-conserved nucleoside-triphosphate-binding motif, which is essential for a variety of biological functions, such as ATPase activity and cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…NS1 is a multifunctional protein that is involved in regulation of viral p6 promoter activity, DNA replication (15)(16)(17), cell cycle arrest in G 1 and G 2 phases in erythroid lineage cells (18,19), and initiation of apoptosis (20). NS1 also functions as a transcriptional transactivator, regulating a variety of viral and cellular genes, such as TNFA (21) and p21 WAF1/CIP1 (22). NS1 contains a nucleoside triphosphate-binding motif relating to NS1 cytotoxicity (23).…”
Section: Introductionmentioning
confidence: 99%
“…The secretion of TNF-␣ and IL-6 induced by the coculture of the macrophage cell line, U937, or THP1 with rheumatoid synovial cells was inhibited by coexistence of monoclonal anti-B19 Abs (12). We also showed that transduction of U937 cells with NS-1 gene-activated transcription factors, AP-1 and AP-2, resulted in the up-regulation of TNF-␣ gene expression and secretion of TNF-␣ from host cells (34). This indicates that persistent activation of B19 may constantly up-regulate the TNF-␣ gene in infected cells.…”
Section: Discussionmentioning
confidence: 62%
“…NS1 is a functional protein of B19 responsible for not only replication of B19 (31), but also activation of host cell genes associated with apoptosis (32) and cytokines (33,34). We have revealed NS1-mediated production of TNF-␣ through activation of AP1 and AP2 (34). The presented data, including an enhanced production of Th1 and Th2 cytokines (Fig.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation